UPPER GASTROINTESTINAL MALIGNANCY IN PATIENTS UNDERGOING ESOPHAGOGASTRODUODENOSCOPY IN SANGLAH GENERAL HOSPITAL DENPASAR - Primadharsinni, Putu Prathiwi (E-Jurnal Medika Udayana, 2014)
<img src="data:image/png;base64,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
Keywords: ESOPHAGOGASTRODUODENOSCOPY,UPPER GASTROINTESTINAL MALIGNANCY